(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
What is kindness in understanding society? This is the person’s desire to help but not expect or ask for anything in return. But that’s certainly not the full definition. Kindness is a very high and powerful emotion, thousands of books have been written about it, hundreds of films have been made. In all fairy tales, legends and sagas, good triumphs over evil. It is the foundation of all religions. But somehow it’s dwindling in the world... A new ideal and a new outlook, a new time. Now, kindness is not a profitable investment at all: neither advertising, nor popularity, nor money. How can you bring this trait back into people’s lives and be kind yourself? This article will address the topic